An Improved Search Approach for Solving Non-Convex Mixed-Integer Non Linear Programming Problems - Sitopu, Joni Wilson; Mawengkang, Herman; Lubis, Riri Syafitri (IOP conference series. Materials Science and Engineering, 2018)
The nonlinear mathematical programming problem addressed in this paper has a structure characterized by a subset of variables restricted to assume discrete values, which are linear and separable from the continuous variables. The strategy of releasing nonbasic variables from their bounds, combined with the "active constraint" method, has been developed. This strategy is used to force the appropriate non-integer basic variables to move to their neighbourhood integer points. Successful implementation of these algorithms was achieved on various test problems.